(untitled) (International Journal of Engineering and Computer Science, 2018)
Vehicular Ad-hoc Networks (VANETs) are generally accepted as an exceptional type of Mobile Ad hoc Network (MANET). VANETs have seen tremendous growth in last decade, providing a vast range of uses in both military as well as civilian activities. The temporary connectivity in the vehicles can also increase the driver’s capability on the road. In this paper, an efficient data dissemination approach is proposed which not only improves the vehicle to vehicle connectivity but also improves the QoS between the source and the destination. The effectiveness of the proposed approach is demonstrated when it comes to the significant gets achieved in the parameters namely, end to end delay, packet loss ratio, average download delay and throughput in comparison with the existing approaches.